Smoke and fog Detection in Images - Francis, Freceena; Mohan, Maya (International Journal of Computer Sciences and Engineering, 2018)
Images of outside scenes are typically degraded by the cloudy or opaque medium in the atmosphere. Haze, fog, and smoke in atmosphere are such phenomena because of atmospheric absorption and scattering. Due to the smoke or fog in the atmosphere, the irradiance received by the camera from the scene point is attenuated along the line of sight. Smoke and Fog in images can be distinguished based on their physical appearance and density variations. To distinguish these images, features such as SIFT, HOG, LBP features are extracted and are trained using SVM classification model. Smoke and Fog in images can be tested successfully that the image belongs to which class after training the images.